ANIMALS, MORAL STATUS, AND THE OBJECTIVES OF MORALITY. Issue 47 (30th October 2017) - Lindsay, Ronald A.
Abstract : Many philosophers maintain that a being's moral status depends on its capacities, for example, whether the being is rational or sentient. In the notorious 'argument from marginal cases', animal rights advocates make use of this received view by arguing that because infants and the severely cognitively disabled have no more capacities than many animals, animals have status equivalent to humans and are entitled to equal moral consideration. But although capacities may be relevant to moral status, they do not determine it. Ultimately, we need to consider the objectives of morality in determining what obligations we have towards any group of beings, whether they are aliens, humans, or animals.